Adoption of BIM software in the Architecture discipline in a Civil Engineering course - Azevedo, Vinícius Francis Braga de; Rodrigues, Igor Alencar; Silva Neto, Vicente Estevam da; Vasconcelos, Bianca M. (Technical and Scientific Journal Green Cities, 2024)
Building Information Modeling (BIM) is recognized as a sustainable approach to the development of architecture and engineering projects, operating at all phases of a building's life cycle. Despite its importance, the adoption of BIM in education has been gradual. The aim of this article is to investigate the adoption of BIM software by civil engineering students at the Polytechnic School of the University of Pernambuco (POLI/UPE) in the architecture course, taught in the 6th semester. The longitudinal study encompassed quantitative data from 2020 to 2023, aiming to classify the delivered projects according to the software used (2D or BIM), identify temporal trends in the use of BIM software, and develop hypotheses to understand the reasons for the software choice. It was observed that the use of 2D software was predominant among students in 2020, with 63.95% usage, but there was a gradual increase in the adoption of BIM software over time, becoming significant in 2023, with 80.85% usage. This study contributes to the understanding of the dynamics related to the integration of BIM in academic training in Civil Engineering, highlighting the role of the university as a promoter of sustainable practices in the construction industry, emphasizing the importance of BIM as a tool for efficiency and quality throughout the building life cycle.
Keywords: Building Information Modeling; Education; Technology.